Agricultural technical schools students’ and teachers’ beliefs about the environment - Parrado Álvarez, Oscar Leopoldo; Castro Torres, Biofredis; Sóñora Revoredo, Humberto Bienvenido (Transformación, 2024)
Objective: The paper aims at assessing the environmental Agricultural Technical schools students’ and teachers’ beliefs  about the environment intended to improve professional training of graduates. Methods: The researchers rely on the Scale of New Ecological Paradigm with 16 items modified for Spanish speakers and the Semantic Differential with 13 pairs of adjectives given to a sample of 72 students and 60 teachers from the Polytechnic Agricultural Institutes Alvaro Barba Machado and Martires de Pino Tres.Result: The scale of the New Ecological Paradigm proved to be reliable in the conditions of Cuba. The analysis reveals there are at least three types of students’ beliefs (moderate ecocentric, ecocentric-bioethic and anthropocentric), whereas teachers' beliefs are characterized by ecocentrism, anthropocentrism, naturalism and awareness of the limits of natural resources.Conclusion: There are differences between teachers and students in relation to their beliefs. The maturity and large experience of the former can be used in the training of students. Postgradute education might be a way to overcome the anthropocentric so that education would be  more effective.
Keywords: environmental education; environmental awareness; environmental believes; profesiional training; agricultural training